PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) DALAM MENINGKATKAN SIKAP GOTONG ROYONG DAN PRESTASI BELAJAR IPAS PADA MATERI KEBUTUHAN MANUSIA DI KELAS IV SD NEGERI 2 TAMBAKSOGRA: Penelitian Tindakan Kelas - Muhamad Nur Ismail; Pamujo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to improve the attitude of mutual cooperation and student learning achievement through the STAD model in learning science and human needs material in class IV. This research was carried out in two cycles with each cycle consisting of two meetings. The research subjects were 21 students. Data was collected using observation sheets, questionnaires, evaluation sheets and documentation. The results of this research show that there is a gradual increase in mutual cooperation attitudes and student learning achievement. In cycle I the students' mutual cooperation attitude reached an average of 34.47 with a percentage of 68.94% (good criteria), and in cycle II it reached an average of 41.19 with a percentage of 82.38% (very good criteria). Likewise with student learning achievement, in cycle I it produces an average score of 64.04 with a learning completeness percentage of 59.52% (sufficient criteria), then in cycle II it produces an average score of 72.61 with a learning completeness percentage of 80 .85% (good criteria). This research shows that the use of the STAD learning model has a positive impact on mutual cooperation attitudes and student learning achievement.